PENGARUH PRODUKSI, LUAS LAHAN, DAN HARGA KELAPA SAWIT TERHADAP PDRB DI KECAMATAN MERLUNG JAMBI - Nurmalita Sari (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
The plantation sector, particularly oil palm, plays a significant role in driving regional economic growth through its contribution to Gross Regional Domestic Product (GRDP). Merlung District in Tanjung Jabung Barat Regency is one of the oil palm plantation centers that provides a substantial contribution to the local economy. This study aims to analyze the effect of production, land area, and price on the GRDP of the plantation sub-sector in Merlung District during the period 2018–2024. This research employs a quantitative approach using multiple linear regression analysis. The data used are secondary quarterly data covering production, land area, fresh fruit bunch (FFB) prices, and GRDP values of the plantation sub-sector. Statistical tests include the t-test to assess partial effects, the F-test to examine simultaneous effects, and the coefficient of determination (R²) to measure the explanatory power of the model. The findings reveal that, partially, production has a significant negative effect on GRDP, while land area and FFB prices have significant positive effects. Simultaneously, the three independent variables significantly influence GRDP, with the calculated F-value exceeding the F-table and a significance level of 0.000 < 0.05. The coefficient of determination indicates that production, land area, and price variables explain most of the variation in GRDP in Merlung District. Therefore, this study highlights the importance of optimal land management, sustainable productivity improvement, and price stabilization policies as key strategies to enhance the plantation sub-sector’s contribution to GRDP in Merlung District.